Phosphate-based mixed polyanionic positive insertion materials for energy storage applications - Lochab, Shubham; Advised by Barpanda, Prabeer (Bangalore : Indian Institute of Science, 2024)
Mixed polyanionic insertion materials offer a rich treasure house to develop robust cathode insertion materials having a desirable combination of chemical and thermal stability, as well as tuneable redox voltage and electrochemical performance [1]. Among them, PO4-based mixed polyanionic compounds stand out due to their scalable synthesis, safe storage and handling, and high energy density. In addition to their intercalation behaviour, they also display interesting magnetic properties and bifunctional electrocatalytic behaviour suited for metal-air batteries. My thesis, combining experimental and modelling tools, is focused on three different types of PO4-based mixed polyanionic insertion materials exploring their electrochemical behaviour, magnetic structure/ properties and electrocatalytic activity as outlined below. (1) Mixed phosphates Na4M3(PO4)2P2O7 (M=Mn, Fe, Co, Ni): Firstly, solution calorimetry was used to determine the thermochemical stability of the entire family of compounds [2]. The electrochemical behaviour of Fe analogue was then examined for sodium-ion batteries (NIBs). A reduced order model (ROM) was validated with experimental data in a full cell configuration using hard carbon as anode [3]. Subsequently, analogous nanoscale Na4Co3(PO4)2P2O7 and Na4Ni3(PO4)2P2O7 were explored as bifunctional electrocatalysts for oxygen evolution and reduction reactions (OER and ORR) [4]. These mixed phosphates are promising for application in rechargeable sodium-ion as well as sodium-air batteries. (2) NASICON-type phosphosulfate: Mixed polyanionic NaFe2PO4(SO4)2 was explored for Li- and Na-ion batteries exploiting its Fe+3/Fe+2 redox couple centered ~3 V with good capacity and cycling stability [5-6]. Spray drying synthesis was conducted to prepare phase-pure compound involving the lowest annealing temperature of 100 °C yielding uniform spherical morphology. It was studied using powder X-ray/ neutron diffraction along with suites of physical and electrochemical characterizations. Low-temperature magnetometry and neutron diffraction revealed a long-range antiferromagnetic ordering below 45 K. NaFe2PO4(SO4)2 was found to be versatile cathode for both Li-ion and Na-ion batteries involving single-phase redox mechanism as probed by in-situ X-ray diffraction. The electrochemical performance was also probed using a single particle model (SPM) as well. (3) Other phosphates: Invoking the inductive effect principle, the electrochemical properties can be altered based on different combination of phosphate groups. The magnetic structure and electrochemical properties of layered iron phosphate Na3Fe3(PO4)4 and fluorophosphates Na2MPO4F (M=Mn, Fe) were probed. Na3Fe3(PO4)4 works as a 2.43 V insertion material for Na-ion batteries having an antiferromagnetic ordering below 27 K [7]. The electrochemical performance of Na2FePO4F fluorophosphate, working as a 3 V NIB cathode, was investigated using electrochemical tools and single particle modeling. While Na2MnPO4F offered poor battery performance, it exhibited a long-range antiferromagnetic ordering below 10.4 K [8].
Includes references.
PhD;2024;Materials Research Centre.
Keywords: Li-ion electrochemistry; Antiferromagnetic; Sodium-ion batteries